Factores y Processos de Formacion de Suelos en el Piedemonte Oriental de la Sierra Chica, Cordoba, Republica Argentina - SACCHI, GABRIELA; PASQUINI, ANDREA (Pesquisas em Geociências, 1999)
This contribution deals with the characteristics and distribution of soils developed over six landscape units in a sector of the eastern Sierra Chica piedmont (Córdoba, Argentina). The relationship between environmental factors and pedogenetic processes have been examined. The area exhibits a significant soil variability as a consequence of geomorphic and lithologic diversity, inherent to this environment. Parental material, relief, and climate have shown influence over soil development and the differentiation of horizons. They control, as well, the intensity of melanization, decalcification-calcification and eluviation-illuviation of clays and organic matter. The most developed soils are derived from loess, loess-like and fine alluvial sediments. These soils are found in areas of intermediate to low relief, concave and flat surfaces, and long-smooth slopes. Fluvial and coarse alluvial sediments are the parental material of less developed soils, which are characteristic of reliefs dominated by rolling shapes and steep slopes.